Risk of cancer in adults with primary immune thrombocytopenia: a binational population-based real-world cohort study from Denmark and France - Nikolaj Mannering; Yoann Zadro; Dennis Lund Hansen; Julien Maquet; Margaux Lafaurie; Anton Pottegård; Guillaume Moulis; Henrik Frederiksen (Haematologica)
Immune dysregulation and immunosuppression occur due to the pathophysiology and management of primary immune thrombocytopenia (ITP), which together may increase the risk of subsequent cancer. We investigated the cancer risk in ITP compared with the general population in a binational cohort study in Denmark and France.